IMPLEMENTASI METODE DEPTH FIRST SEARCH PADA SISTEM PAKAR KONSULTASI BANTUAN HUKUM CERAI GUGAT - Rabbil Budiman; Rachmat Wahid Saleh Insani; Alda Cendekia Siregar (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2026)
The problem of divorce, especially in Pontianak city, has increased significantly, but community access to legal information and services is often hampered by a lack of legal understanding, creating a gap in justice that can lead to other social problems. Therefore, this research focuses on the development of an expert system that utilizes the depth first search (DFS) method to provide consultation results on legal issues of contested divorce based on the compilation of Islamic law. The research methods include problem identification, data collection through interviews with legal experts followed by design using the waterfall method to ensure the system runs well. The test results show that the depth first search method is able to provide fast and accurate consultation results regarding the problems faced by wives who want to divorce based on the results of testing the accuracy of the system by comparing the results of system diagnosis and experts obtained 80% results so it is concluded that the accuracy of the system made is considered successful.